Variation in clinical practice in genitourinary medicine clinics in the United Kingdom. Issue 3 (1st June 2003) - Carne, C A; Foley, E; Rowen, D; Kell, P; Maw, R
Abstract : Objectives: This study was conducted to examine the variation in clinical practice in genitourinary medicine clinics in the United Kingdom in early 2002. Methods: Questionnaires were sent to all 234 consultants in charge of genitourinary medicine clinics in the United Kingdom in March-May 2002. The questions concerned clinical practice in respect of asymptomatic patients presenting for an infection screen, and practice in respect of some specific sexually transmitted and other genitourinary infections. Results: The test for infection least likely to be offered to heterosexuals is an HIV test (71% and 70% of clinics routinely offer this to male and female heterosexuals respectively). The practice of permitting "low risk" patients to telephone for their HIV results now extends to 24% of clinics. 34% of clinics do not require patients with non-specific urethritis to attend for follow up. 41% of clinics routinely ask patients treated for Chlamydia trachomatis to return for a follow up chlamydia detection test. 25% of clinics routinely offer two tests of cure to all patients with gonorrhoea. 6% of clinics do not routinely offer syphilis serology to heterosexuals. Other significant variations in clinical practice were documented. Conclusions: Overall, our findings indicate the need for further evidence to guide clinical practice and a wider knowledge and debate of national guidelines.